Transcriptional Activation by ETS and Leucine Zipper-Containing Basic Helix-Loop-Helix Proteins - Tian, Gang (American Society for Microbiology, 1999)
The immunoglobulin μ heavy-chain gene enhancer contains closely juxtaposed binding sites for ETS and leucine zipper-containing basic helix-loop-helix (bHLH-zip) proteins. To understand the μ enhancer function, we have investigated transcription activation by the combination of ETS and bHLH-zip proteins. The bHLH-zip protein TFE3, but not USF, cooperated with the ETS domain proteins PU.1 and Ets-1 to activate a tripartite domain of this enhancer. Deletion mutants were used to identify the domains of the proteins involved. Both TFE3 and USF enhanced Ets-1 DNA binding in vitro by relieving the influence of an autoinhibitory domain in Ets-1 by direct protein-protein associations. Several regions of Ets-1 were found to be necessary, whereas the bHLH-zip domain was sufficient for this effect. Our studies define novel interactions between ETS and bHLH-zip proteins that may regulate combinatorial transcription activation by these protein families.